Targeting Oxidative Stress and Inflammation in Intervertebral Disc Degeneration: Therapeutic Perspectives of Phytochemicals - Kang, Liang; Zhang, Huaqing; Jia, Chongyu; Zhang, Renjie; Shen, Cailiang (Frontiers in Pharmacology, 2022)
Low back pain is a major cause of disability worldwide that declines the quality of life; it poses a substantial economic burden for the patient and society. Intervertebral disc (IVD) degeneration (IDD) is the main cause of low back pain, and it is also the pathological basis of several spinal degenerative diseases, such as intervertebral disc herniation and spinal stenosis. The current clinical drug treatment of IDD focuses on the symptoms and not their pathogenesis, which results in frequent recurrence and gradual aggravation. Moreover, the side effects associated with the long-term use of these drugs further limit their use. The pathological mechanism of IDD is complex, and oxidative stress and inflammation play an important role in promoting IDD. They induce the destruction of the extracellular matrix in IVD and reduce the number of living cells and functional cells, thereby destroying the function of IVD and promoting the occurrence and development of IDD. Phytochemicals from fruits, vegetables, grains, and other herbs play a protective role in the treatment of IDD as they have anti-inflammatory and antioxidant properties. This article reviews the protective effects of phytochemicals on IDD and their regulatory effects on different molecular pathways related to the pathogenesis of IDD. Moreover, the therapeutic limitations and future prospects of IDD treatment have also been reviewed. Phytochemicals are promising candidates for further development and research on IDD treatment.